Management of Sports Extracurricular in High Schools Located in Tarakan City - Karnadi Karnadi; Tri Ani Hastuti (International Journal of Studies in International Education, 2025)
This study aims to describe and provide recommendations regarding the proper management of extracurricular sports activities in senior high schools in Tarakan City. Extracurricular activities play an important role in helping students develop their potential. This study used a qualitative descriptive method. Subjects included principals, physical education teachers or extracurricular sports coordinators, and sports coaches from 14 randomly selected religious, public, and private senior high schools in Tarakan City. Data collection techniques included observation, interviews, and documentation. Data validity was ensured through source triangulation and technique triangulation. The data analysis process included data collection, data reduction, data presentation, and drawing conclusions. The research findings indicate that: (1) Planning for extracurricular sports activities is generally carried out through coordination meetings among the parties involved to organize activities during one school year. Scheduling is the responsibility of the extracurricular coordinator and is arranged in consultation with the sports supervisor or coach to avoid conflicts with other school events. Coaches also prepare training programs as part of the planning process. (2) Extracurricular sports activities are held in the afternoon, outside of regular school hours, based on a schedule prepared by the coordinator and vice principal for student affairs. (3) Evaluations are conducted at least once every three months and involve various school stakeholders. Aspects evaluated include student attendance, participation in learning, and training outcomes. (4) Supporting factors include adequate facilities and infrastructure, funding, student competency, and teacher involvement. Conversely, inhibiting factors include low student attendance, limited funding, inadequate or inadequate facilities, and unfavorable weather conditions. These findings provide an overview of how extracurricular sports activities are managed in high schools in Tarakan City and highlight the importance of effective planning, implementation, and evaluation. This study also identifies key factors that support and hinder the success of these programs, offering insights for future improvements.